Experimental investigation of solar-reflective coatings as thermal insulators for rails in heavy-haul corridors - Leal, Carlos Artur Alevato; Paiva, Maria Rita Pereira de; Silva, Stephany Cristina da; Ribeiro, Felipe Ramon de Araújo; Ferreira Junior, Carlos Eduardo Gonçalves; Nunes, Larissa Fernandes; Caneschi, Fernando Paulo; Pacheco, Philipe Augusto de Paula (Brazilian Journal of Production Engineering, 2025)
Rails are critical components of railway infrastructure, responsible for distributing loads, guiding vehicles, and ensuring operational safety. However, temperature variations and solar irradiance induce thermal stress, leading to rail expansion and contraction, as well as potential buckling. While previous studies have explored rail profile optimization and lubrication strategies, limited research exists on thermal mitigation through coatings. This study evaluates the effectiveness of three commercial coatings in reducing rail temperature variations on AREMA 136RE rails under real environmental conditions. Thermocouples monitored temperature changes on coated and uncoated rail samples over multiple seasons, while a pyranometer recorded solar irradiance. Results indicate that coated rails exhibited significantly lower peak temperatures compared to uncoated rails, with maximum reductions exceeding 10°C in summer. Coatings with nanometric hollow ceramic spheres demonstrated superior thermal performance. They maintained temperatures 8–10% lower than Alkyd resin-based coatings on semi-drying vegetable oil when temperatures exceeded 20°C. Seasonal analysis confirmed consistent behavior, with temperature differentials decreasing in cooler months. The findings suggest that reflective coatings can mitigate thermal buckling risks, particularly in tight curves (radius < 50 m), where critical temperature differentials are below 20°C.
Keywords: Trilho; Expansão térmica; Flambagem térmica; Revestimento de trilhos; Movimentação térmica